Pengaruh Current Ratio, Debt To Equity Ratio, Dan Net Profit Margin Terhadap Pertumbuhan Laba Bersih Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia ( Studi Kasus Pada Perusahaan Farmasi Yang Terdaftar di Bursa Efek Indonesia Periode 2019- - Irma Sofia; Enny Arita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to examine the influence of the current ratio, debt to equity ratio, and net profit margin on the net profit growth of pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study was the pharmaceutical sector, the sampling technique used purposive sampling technique, and 11 samples were obtained. The analytical methods used are descriptive anlysis, Classical Assumption Testing and Hypothesis Testing. The result of this research show that the Current Ratio (CR) has a negative effect on the growth of net profit of pharmaceutical sector manufacturing companies with a calculated t value of -1,047 < t table 3,18, Debt To Equity Ratio (DER) has a negative effect on the net profit growth of pharmaceutical sector manufacturing companies with the calculated t value is -0,141 < t table 3,18, and Net Profit Margin (NPM) has a negative effect on the growth of net profit of pharmaceutical sector manufacturing companies with the calculated t value -0,42 < t table 3,18 while simultaneously the Current Ratio (CR), Debt To Equity Ratio (DER), and Net Profit Margin (NPM) have a positive and significant effect on the net profit growth of pharmaceutical sector manufacturing companies with a calculated f value of 0,381 < f table 0,0283.